Comparative Evaluation of Textural and Sensory Characteristics of Sourdough Bread Produced Using Botanical Water from Different Raisin Varieties - Monika Rahardjo; Monang Sihombing; Sekar Eka Wahyuningtyas (JFCN: Journal of Food, Culinary, and Nutrition, 2026)
This study evaluated the effects of botanical water from various raisin varieties on the sensory and textural qualities of sourdough bread. Black, green, and yellow raisins were used to make botanical water, which was then used as a natural fermentation medium. Conventional sourdough was used as the control. Hardness, cohesiveness, springiness, gumminess, chewiness, fracture force, adhesiveness, and stiffness were all measured by texture analysis. Fifty-five untrained panelists used a five-point hedonic scale to rate sensory acceptance. Significant differences were noted in hardness, springiness, gumminess, and stiffness; however, other textural parameters showed no significant variation. Hardness, gumminess, springiness, and stiffness values were highest in sourdough made with yellow raisin botanical water, while the control had the lowest hardness. The sourdough samples stayed within the acceptable range in the sensory evaluation, but the control sample scored highest for color, texture, and overall acceptability. Among the botanical water treatments, green raisin sourdough was the most well-liked. According to the findings, raisin botanical water has an impact on bread structure and fermentation behavior, resulting in quantifiable texture changes and mild variations in sensory perception. Therefore, it is possible to use botanical water from raisins as a natural fermentation medium for making sourdough bread without experiencing severe sensory rejection.